2015
DOI: 10.1152/japplphysiol.00389.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular and ventilatory responses to acute isocapnic hypoxia in healthy aging and lung disease: effect of vitamin C

Abstract: Acute hypoxia increases cerebral blood flow (CBF) and ventilation (V̇e). It is unknown if these responses are impacted with normal aging, or in patients with enhanced oxidative stress, such as (COPD). The purpose of the study was to 1) investigate the effects of aging and COPD on the cerebrovascular and ventilatory responses to acute hypoxia, and 2) to assess the effect of vitamin C on these responses during hypoxia. In 12 Younger, 14 Older, and 12 COPD, we measured peak cerebral blood flow velocity (V̄p; inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 51 publications
1
29
3
Order By: Relevance
“…Differences between the findings of Hartmann et al. () and the present study may be explained by their use of TCD to obtain velocity and not flow, because recent evidence has suggested that the MCA dilates in hypoxia (Verbree et al., ), and that using only MCAv would ultimately underestimate CBF (Hoiland & Ainslie, ). In the present study, we observed dilatation within the ICA during both hypercapnia and acute hypoxia trials.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Differences between the findings of Hartmann et al. () and the present study may be explained by their use of TCD to obtain velocity and not flow, because recent evidence has suggested that the MCA dilates in hypoxia (Verbree et al., ), and that using only MCAv would ultimately underestimate CBF (Hoiland & Ainslie, ). In the present study, we observed dilatation within the ICA during both hypercapnia and acute hypoxia trials.…”
Section: Discussioncontrasting
confidence: 78%
“…() reported a decrease in MCAv reactivity to isocapnic hypoxia in young healthy participants after i.v . infusion of vitamin C (3 g; Hartmann et al., ). Differences between the findings of Hartmann et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar isocapnic hypoxic ventilatory response at rest has been observed in young and older men and women (Smith et al 2001;Pokorski et al 2004;Vovk et al 2004), whereas others have reported reduced isocapnic hypoxic ventilatory responses in older men and women (Kronenberg & Drage, 1973;Serebrovskaya et al 2000;García-Río et al 2007;Hartmann et al 2015). The evaluation of the effect of ageing on the ventilatory response has led to contrasting results.…”
Section: Introductionmentioning
confidence: 81%
“…The cerebrovascular response to hypercapnia in older individuals was reported to be similar (Davis et al 1983;Kastrup et al 1998;Galvin et al 2010;Murrell et al 2012) or reduced (Yamamoto et al 1980;Reich & Rusinek, 1989) compared with younger individuals. Only one study recently evaluated the hypoxic cerebrovascular response in older individuals at rest and reported blunted cerebral blood velocity sensitivity to hypoxia compared with young control subjects (Hartmann et al 2015). At the muscle level, reduced oxygenation has been reported in older individuals at rest and during exercise in normoxia (Costes et al 1999;Ferri et al 2007).…”
Section: Introductionmentioning
confidence: 99%